Anesthesia Management in a Neonate with Esophageal Atresia Undergoing Esophagotomy and Thoracotomy: A Case Report - Galih Puspitasari; Muhammad Ridho Aditya; Raden Theodorus Soepraptomo (HM Publisher, 2025)
Background: Esophageal atresia (EA) and tracheoesophageal fistula (TEF) are congenital anomalies requiring surgical repair in the neonatal period. Anesthetic management for these cases is complex, involving careful planning and execution to ensure a safe perioperative course. This case report details the anesthetic challenges and management of a neonate with EA undergoing thoracotomy and esophagotomy. Case presentation: A five-day-old male infant presented with EA, pneumonia, and sepsis. After preoperative optimization, the neonate underwent thoracotomy and esophagotomy under general anesthesia with invasive monitoring. The perioperative course was complicated by the patient's comorbidities, requiring meticulous airway management, hemodynamic monitoring, and temperature regulation. Conclusion: Successful anesthetic management of neonates with EA undergoing thoracotomy necessitates a multidisciplinary approach, addressing the unique challenges posed by the condition and associated comorbidities. This case highlights the importance of preoperative optimization, careful intraoperative management, and vigilant postoperative care in achieving a positive outcome.